Phosphatidic acid-enabled MKL1 contributes to liver regeneration: Translational implication in liver failure - Jiawen Zhou; Xinyue Sun; Xuelian Chen; Huimin Liu; Xiulian Miao; Yan Guo; Zhiwen Fan; Jie Li; Yong Xu; Zilong Li (Elsevier, 2024)
Liver regeneration following injury aids the restoration of liver mass and the recovery of liver function. In the present study we investigated the contribution of megakaryocytic leukemia 1 (MKL1), a transcriptional modulator, to liver regeneration. We report that both MKL1 expression and its nuclear translocation correlated with hepatocyte proliferation in cell and animal models of liver regeneration and in liver failure patients. Mice with MKL1 deletion exhibited defective regenerative response in the liver. Transcriptomic analysis revealed that MKL1 interacted with E2F1 to program pro-regenerative transcription. MAPKAPK2 mediated phosphorylation primed MKL1 for its interaction with E2F1. Of interest, phospholipase d2 promoted MKL1 nuclear accumulation and liver regeneration by catalyzing production of phosphatidic acid (PA). PA administration stimulated hepatocyte proliferation and enhanced survival in a MKL1-dependent manner in a pre-clinical model of liver failure. Finally, PA levels was detected to be positively correlated with expression of pro-regenerative genes and inversely correlated with liver injury in liver failure patients. In conclusion, our data reveal a novel mechanism whereby MKL1 contributes to liver regeneration. Screening for small-molecule compounds boosting MKL1 activity may be considered as a reasonable approach to treat acute liver failure.